Evaluation of platelet-rich plasma gel potential in acceleration of wound healing duration in patients underwent pilonidal sinus surgery: A randomized controlled parallel clinical trial. Issue 2 (April 2017) - Mohammadi, Saeed; Nasiri, Shirzad; Mohammadi, Mohammad Hossein; Malek Mohammadi, Ashraf; Nikbakht, Mohsen; Zahed Panah, Mahdi; Safar, Hiva; Mostafaei, Shayan; Norooznezhad, Amir Hossein; Soroosh, Ahmad Reza; Alimoghaddam, Kamran; Ghavamzadeh, Ardeshir
Abstract: Objectives: One of the most important surgical issues applied in the treatment of pilonidal sinus disease is wound healing. The aim of this study was to investigate the possible effect of platelet-rich plasma (PRP) gel on accelerating wound healing in these patients. Methods: In this randomized, controlled, parallel group clinical trial, 110 patients were randomly allocated into two parallel groups with the same size (controls and treatment arm) after meeting inclusion and exclusion criteria. After the surgery, controls were treated by classic wound dressing while the case group was treated with PRP gel in a classic wound dressing platform. The patients were then evaluated for duration of antibiotics consumption, experienced pain and the time of returning to routine activities. Also, both groups were assessed for angiogenesis (by detecting CD34 + cells using immunohistochemical assay) and collagen sedimentation (masson's trichrome staining) using pre-complete healing wound biopsy. All the statistical analyses were performed using SPPS 20 and p-values of less than 0.05 considered statically significant. Results: According to the results, patients treated with PRP gel went through a significantly faster healing process (8.69 ± 1.18 in controls and 4.78 ± 0.87 weeks in PRP gel treated ones with the P-value = 0.03) and returned to their routine activities (3.3 ± 0.64 for the treatment of arm and 6.5 ± 1.03 weeks for controls with the P-value = 0.00) while experiencing less pain (P-value = 0.00) and shorter anti-biotic consumption duration (P-value = 0.00). Conclusion: Considering the results, authors of this study suggest PRP gel treatment for post operation wound dressing of pilonidal sinus disease with healing by secondary intention.